DILEMA IDENTITAS DAN KOLONIALISASI TUBUH: ANALISIS SOSIOLOGI STANDAR KECANTIKAN GLOBAL PADA PEREMPUAN GENERASI Z DI INDONESIA - Alifiya Zahwa Nabila; Syamsul Bakhri (Yayasan Literasi Sains Indonesia, 2025)
The development of social media in the digital era has reshaped the ways beauty is understood, particularly among Generation Z women in Indonesia. Modern beauty standards that emphasize fair skin, slim bodies, and idealized appearances are widely disseminated through social media, popular culture, and the beauty industry, creating social pressure that influences how women perceive themselves and their bodies. This study aims to analyze how global beauty standards are constructed and reproduced through social media, as well as how such social pressure is experienced by Generation Z women in their everyday social lives. This research employs a library research method with a qualitative descriptive approach by reviewing books and scholarly articles published between 2022 and 2025 that are relevant to beauty standards, social media, and Generation Z women. The findings indicate that modern beauty standards are social constructs that function as mechanisms of social control over women’s bodies. Social pressure emerges through processes of social comparison, body shaming practices, beauty privilege, and the commodification of women’s bodies in digital spaces. These conditions affect the formation of negative self-image, reduced self-confidence, increased psychosocial vulnerability, and the encouragement of consumptive behavior among Generation Z women. In addition, beauty standards reinforce gender inequality and symbolic violence that operate subtly through social norms perceived as natural and unquestioned. Overall, this study demonstrates that beauty standards are not merely aesthetic concerns but are embedded within social mechanisms that shape identity, social relations, and the psychosocial well-being of Generation Z women in Indonesia.